Pruritus in diabetes mellitus (DM) and its pathophysiology-based treatment - Lorettha Wijaya; Audrey Melanie; Veronica Veronica; Gabriela Christy (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2022)
Pruritus is a common complaint of diabetic patients with a substantial impact on financial and health status, but the pathophysiology is unclear and treatment with antihistamines has mostly been unsuccessful. To date, we still do not have guidelines to help us treat pruritus in diabetes mellitus, so we felt the need to review the existing literature to explore possible ways to treat these patients. We collected 85 pieces of literature from various sources such as PubMed and Google Scholar, and independently extracted these data to make this review. While the pathophysiology behind pruritus in diabetes mellitus remains largely unknown, some trials have found a few pharmacological treatments to be effective in alleviating itch in these patients.